Sustainable school feeding innovations in Kigali: Baseline survey report - Munyangeri, Yvonne; Mutua, Mercy; Rurangwa, Edouard; Ngabire, Sam; Dusabimana, Emmanuel; Tuyishime, Omar; Rubyogo, Jean Claude; Birachi, Eliud A (2024)
This report presents the findings of a baseline survey conducted for the Sustainable School Feeding Innovations in Kigali (SSFI) project. The three-year project, supported by Clifford Chance, aims to implement nutrition-sensitive school feeding innovations in Kigali city schools and surrounding communities. The project uses a value-chain-based approach to enhance skills in producing, utilizing, and supplying nutritious foods to schools and other markets in Kigali. The survey provides a baseline assessment of the state of the school feeding program in Kigali city schools. The survey sampled 195 schools with a school feeding program in three districts of Kigali city: Gasabo (75 schools), Kicukiro (65 schools), and Nyarugenge (55 schools). Respondents were mainly heads of schools, head teachers, and school accountants. The baseline results include school ownership indicators, the number of students, the governance of the school feeding program, key school meals, cooking fuel, bean consumption, awareness and adoption of pre-cooked beans, school gardens, best agronomic practices, and climate knowledge. The project evaluation will assess changes over time in these benchmark indicators and compare the changes and impact in the schools that benefited from project interventions and those that did not. According to the survey, the school feeding program is available in all 195 surveyed schools with 277,566 students (49.8% boys and 50.2% girls). Most schools are public or government-aided, mainly purely day schools (92.8%). The school feeding program is managed by the school feeding committee, which comprises two parents’ representatives, the head teacher, the school secretary, two teachers’ representatives, two representatives of students, the store manager, and a representative of cooks. The committee oversees the procurement process and food menus, ensuring the quality and quantities of food students eat are suitable, among other responsibilities. Key meals in the school feeding program are breakfast, lunch, and dinner for purely boarding and mixed schools and lunch only for purely day schools. The school feeding program is mainly funded by the government, contributing 89% of the cost, and parents contribute 11%. Survey results also show that beans are the staple served in schools (97%), followed by rice (86%) and maize (71%), with beans being served mainly for lunch and supper. 100% of public and government-aided schools and 92% of private schools serve beans daily. The survey also revealed that firewood (85.6%) and charcoal (11.8%) are schools’ main sources of cooking energy. Other sources of cooking energy are gas (4.6%) and pellets (0.5%). However, the survey also highlighted that there is a high cost attached to the high dependence on biomass fuel for cooking in Kigali schools, with up to 40 hours a week dedicated to cooking fuel and $29,453.4 spent for cooking wages, of which $19,770 is spent on cooking dry beans only per month. Dry beans are cooked 5 to 7 times per week, and at least 52 tons of dry beans are cooked weekly, taking 48.5 cubic meters of water to clean and cook beans daily in the 195 schools. Among the schools surveyed, only 46% of school representatives are aware of pre-cooked beans, with two schools (both private) using pre-cooked beans in their meals, while the rest use dry beans. The low adoption of pre-cooked beans in schools is attributed to a lack of awareness of pre-cooked beans, little trust in the sustainability of the supply of pre-cooked beans, high prices, low availability, and little trust in the quality of pre-cooked beans. 73% (145 out of 195) of schools surveyed have school gardens established mainly for food production (89%) and teaching (11%). Beans are among the top three crops grown in school gardens, as are vegetables and bananas. However, their yield can’t suffice the needs of schools even though some schools have up to 2 hectares of land. Capacity building on best agronomic practices and climate-smart agriculture is recommended for school gardening to improve the yield of beans and vegetables, which are part of daily school meals. The survey also found that the school feeding program contributes to attendance, reduced dropouts, completion of studies and ultimately improved nutrition of school children. Keywords School feeding, cooking fuel, pre-cooked beans, school garden, climate-smart agriculture, Kigali City